Demarcating Boundaries: Against the “Humanitarian Embrace” - Brankamp, Hanno (Refuge, 2021)
Recent years have seen recurrent calls for bridging the “gap” between the worlds of policy-makers, practitioners, and academic scholars concerned with forced migration and humanitarian aid. This has resulted in growing partnerships between international organisations, governments, businesses, foundations, and universities with the aim of harnessing market economic thinking to create new practice-oriented knowledge rather than out-of-touch theories. This intervention responds critically to these developments and questions the seemingly common-sense logic behind attempts to forge ever closer collaborations across institutional lines. Rather than benefitting displaced communities, bridging divides has often served as a way of consolidating the hegemony of humanitarian actors and inadvertently delegitimized more critical scholarship. Scholars in refugee and forced migration studies have hereby been engulfed in a tightening “humanitarian embrace”. This paper argues that in order to fulfil a scholarly commitment to social justice, anti-violence and pro-asylum politics, it is time to again demarcate the boundaries between the practices and institutions that reproduce humanitarian power and their critics.